2020
DOI: 10.20453/rmh.v30i4.3665
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic scar after cleft lip repair: Review of the current treatment

Abstract: La fisura labial -con o sin fisura palatina- es la malformación congénita facial más frecuente a nivel mundial que requiere cirugía -queiloplastía- para ser corregida. Desafortunadamente, la cicatriz hipertrófica posqueiloplastía es un resultado común que afecta negativamente al paciente, su entorno social e incluso a los especialistas, pues a la fecha no existe tratamiento específico. Con el objetivo de conocer el estado actual del tratamiento de dicho problema, se realizó una revisión bibliográfica desde el … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…4 Several modalities are described as effective in treating cheiloplasty lip scars, such as laser, silicone, botulinum toxin, IPL, and massage. [5][6][7][8] Scar massage is the therapeutic manipulation of soft tissue formed during tissue repair and delivered primarily by hands. 9 It has been suggested that massage can reduce postoperative fibrosis, increase the flexibility of scars, and decrease adhesions to the deep plane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Several modalities are described as effective in treating cheiloplasty lip scars, such as laser, silicone, botulinum toxin, IPL, and massage. [5][6][7][8] Scar massage is the therapeutic manipulation of soft tissue formed during tissue repair and delivered primarily by hands. 9 It has been suggested that massage can reduce postoperative fibrosis, increase the flexibility of scars, and decrease adhesions to the deep plane.…”
mentioning
confidence: 99%
“…Several modalities are described as effective in treating cheiloplasty lip scars, such as laser, silicone, botulinum toxin, IPL, and massage 5–8 …”
mentioning
confidence: 99%